Pengaruh Beban Kerja terhadap Kinerja Karyawan Bagian Produksi pada PT Soraya Bedsheet Pekanbaru - Elida Gultom (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This study aims to determine the effect of workload on the performance of employees in the Production department at PT Soraya Bedsheet Pekanbaru. This analysis uses independent variables, namely workload and dependent variables, namely employee performance. The sample of this study was 70 production employees. The data analysis technique used Simple Linear Regression analysis with hypothesis testing of statistical tests, T-test. The results of this study indicate that workload has a significant effect on the performance of production employees at PT Soraya Bedsheet Pekanbaru.